Retinol levels in serum and chronic skin lesions of atopic dermatitis - Rabindranath Biswas; Goutam Chakraborti; Kheya Mukherjee; Debojyoti Bhattacharjee; Sabyasachi Mallick; Tanmoy Biswas (Wolters Kluwer Medknow Publications, 2018)
Background: Atopic dermatitis (AD) is a common childhood dermatosis and a distressing cause of morbidity. The pathogenesis of AD is known to be associated with disorders of immune response and defect in antioxidant defense, genetic predisposition, environmental triggers, psychosomatic factors, and other mechanisms. Retinol has immunomodulatory and antioxidant effects, thus may have a protective role in AD. Objective: The objective of this study was to evaluate the correlation of retinol levels in skin lesions and serum, with AD. Materials and Methods: The study was a hospital-based, case-control study. Punch biopsy from the skin and venous blood of 86 participants (including 43 cases and 43 controls) were assayed for retinol levels by a reversed-phase high-performance liquid chromatography method. Analysis of data was performed using appropriate statistical methods. Results: Skin and serum retinol levels were highly significantly decreased in patients in respect to that of controls. Conclusion: Retinol levels were decreased in AD. Retinol estimation may be used as a promising parameter for the elaboration of treatment strategy and monitoring.